Ask Question
28 March, 15:22

Which expression is equivalent to (-9x^-1 y^-9) / (-15x^5 y^-3) ? assume x = / 0 y = / 0

0
Answers (1)
  1. 28 March, 16:50
    0
    The answer is 3/5x^6y^6

    Step-by-step explanation:

    The given expression is:

    -9x^-1 y^-9/-15x^5 y^-3

    It can be written as:

    = - 9/-15 * x^-1/x^5 * y^-9/y^-3

    As we know that [x^m/x^n = x^m-n]

    = 3/5 * x^-1-5 * y^-9+3

    = 3/5 * x^-6 * y^-6

    = 3/5 * 1/x^6 * 1/y^6

    = 3/5x^6y^6

    The answer is 3/5x^6y^6 ...
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Which expression is equivalent to (-9x^-1 y^-9) / (-15x^5 y^-3) ? assume x = / 0 y = / 0 ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers